Maizy's snowy day - Cousin, Lucy (London Walker Books Ltd, 2022)
It's a snow day! Join Maisy and her friends for a flurry of fun in this new Maisy's First Experiences book. Wrap up warm to throw snowballs and catch snowflakes, build a snow mouse, set off on a sled race and drink a delicious mug of hot chocolate
Keywords: English story book